Waste Management Capacity of Micro and Small Enterprises: Case Study at Panjang Beach, Bengkulu, Indonesia - Titi Darmi; Iqbal Miftakhul Mujtahid; Dwi Kristanti (Yayasan Darussalam Bengkulu, 2026)
Background: Micro and small enterprises (MSEs) operating in the coastal area of Panjang Beach, Bengkulu, Indonesia, generate waste that significantly disrupts visitors' experiences and negatively impacts the environment and the area's appeal. This study aimed to analyze the capacity of MSE owners to manage waste in this region. Method: This research employed a qualitative approach with content analysis. Purposive sampling was used to select ten informants, with data sources categorized as primary and secondary. Data were analyzed using qualitative methods to examine waste management practices and the challenges faced by MSE owners in the coastal tourism area. Results: The findings reveal that MSE owners' waste management capacity needs to be improved, as they struggle to separate organic from non-organic waste and often resort to burning to address waste accumulation. The study also highlights a lack of empowerment and guidance from stakeholders, emphasizing the urgent need for interventions and support mechanisms to improve waste management practices among MSE owners. The research underscores the critical role of institutional capacity at the local government level in fostering collaborative governance and effective waste management strategies. Conclusion: This research contributes to the literature on environmental management and small business sustainability by applying the ecological balance model within the context of coastal tourism areas. By exploring the reciprocal relationship between MSEs and their environment, this study highlights the importance of building institutional capacities to address complex socio-environmental challenges, ultimately supporting sustainable tourism development in coastal regions.